Changing seasonality of convective events in the Labrador Sea - Zhang, Fan (Georgia Institute of Technology, 2014)
The representation of deep convection in ocean models is a fundamental challenge for climate science. Here a regional simulation of the Labrador Sea circulation and convective activity obtained with the Regional Oceanic Modeling System (ROMS) over the period 1980-2009 is used to characterize the response of convection to atmospheric forcing and the variability in its seasonal cycle. This integration compares well with the sparse in time and space hydrographic surveys and ARGO data (Luo et al. 2012). It is found that convection in the convective region of the Labrador Sea has experienced variability in three key aspects over the 30 years considered. First, the magnitude of convection varies greatly at decadal scales. This aspect is supported by the in-situ observations. Second, the initiation and peak of convection (i.e. initiation and maximum) shift by two to three weeks between strong and weak convective years. Third, the duration of convection varies by approximately one month between strong and weak years. The last two changes are associated to the variability of winter and spring time heat fluxes in the Labrador Sea, while the first results from changes in both atmospheric heat fluxes and oceanic conditions through the inflow of warm Irminger Water from the boundary current system to the basin interior. Changes in heat fluxes over the Labrador Sea convective region are strongly linked to large scale modes of variability, the North Atlantic Oscillation and Arctic Oscillation. Correlations between the mode indices and the local heat fluxes in the convective area are largest in winter during strong, deep events and in spring whenever convection is shallow. M.S.